A comparison of natalizumab’s effects on SDMT between pediatric-onset and adult-onset multiple sclerosis patients - Puthenparampil, Marco; Scialpi, Graziana; Gaggiola, Marta; Zanotelli, Giovanni; Miscioscia, Alessandro; Berardi, Angela; Riccardi, Alice; Nosadini, Margherita; Sartori, Stefano; Perini, Paola; Rinaldi, Francesca; Gallo, Paolo (Frontiers in Neurology, 2024)
Background Pediatric-onset multiple sclerosis (POMS) patients often exhibit a wide range of cognitive deficits. Therefore, therapeutic approaches should aim not only to prevent cognitive decline but also to promote cognitive improvement. Objective This study aimed to explore the effects of natalizumab (NTZ) on cognitive function, as measured by the Symbol Digit Modalities Test (SDMT), in both POMS and adult-onset multiple sclerosis (AOMS) patients. Method A total of 63 patients (34 AOMS and 29 POMS) were enrolled in this retrospective, single-center study. Patients were clinically and radiologically assessed every 6 months, and they completed the SDMT at baseline and after at least 24 months of follow-up. SDMT values were reported as corrected values (cSDMT) and z-scores (zSDMT). Annualized cSDMT and zSDMT scores were calculated by dividing the change in scores by the length of the follow-up period (expressed in years). Results Both POMS and AOMS groups showed improvement in annualized cSDMT and zSDMT scores, but the improvement was significantly greater in the POMS group compared to the AOMS group (+3.85 ± 4.32 vs. +1.76 ± 2.80, p = 0.010 for cSDMT; 0.41 ± 0.40 vs. 0.25 ± 0.34, p = 0.026 for zSDMT). After re-baselining at 6 months, 93% of POMS patients (27 patients) and 85.3% of AOMS patients (29 patients, p = 0.84) achieved NEDA-3 (no evidence of disease activity). The NEDA-3 status, along with clinical and demographic parameters at baseline, did not account for the observed SDMT improvement. Conclusion The favorable clinical, radiological, and neuropsychological outcomes observed in this study support the use of natalizumab as a viable treatment option in POMS.